In utero nanoparticle delivery for site-specific genome editing - Ricciardi, Adele S.; Bahal, Raman; Farrelly, James S.; Quijano, Elias; Bianchi, Anthony H.; Luks, Valerie L.; Putman, Rachael; López-Giráldez, Francesc; Coşkun, Süleyman; Song, Eric; Liu, Yanfeng; Hsieh, Wei-Che; et al. (Nature communications, 2018)
Genetic diseases can be diagnosed early during pregnancy, but many monogenic disorders continue to cause considerable neonatal and pediatric morbidity and mortality. Early intervention through intrauterine gene editing, however, could correct the genetic defect, potentially allowing for normal organ development, functional disease improvement, or cure. Here we demonstrate safe intravenous and intra-amniotic administration of polymeric nanoparticles to fetal mouse tissues at selected gestational ages with no effect on survival or postnatal growth. In utero introduction of nanoparticles containing peptide nucleic acids (PNAs) and donor DNAs corrects a disease-causing mutation in the β-globin gene in a mouse model of human β-thalassemia, yielding sustained postnatal elevation of blood hemoglobin levels into the normal range, reduced reticulocyte counts, reversal of splenomegaly, and improved survival, with no detected off-target mutations in partially homologous loci. This work may provide the basis for a safe and versatile method of fetal gene editing for human monogenic disorders. The correction of genetic defects in utero could allow for improved outcomes of gene therapy. Here, the authors demonstrate safe delivery of nanoparticles to fetal mouse tissues, and show that nanoparticles containing peptide nucleic acids to edit the beta-globin gene are effective in a mouse model of beta-thalassemia.